Surgical Skills Olympiad: A 4-Year Experience in a General Surgery Residency Program - Oberoi, Kurun P. S.; Caine, Akia D.; Schwartzman, Jacob; Livingston, David H.; Merchant, Aziz M.; Kunac, Anastasia (The Surgery Journal, 2021)
Background The acquisition of operative skills is the critical defining component of general surgery training. Performing simulated tasks has been shown to increase a resident's technical skills. As such, we devised the Surgical Skills Olympiad, an annual simulation-based skills competition. We examined our 4-year experience with the Olympiad at a large academic general surgery residency program.Objective This study aimed to use competition to motivate trainees to increase the time they spent practicing basic surgical skills, resulting in improved performance over time.Methods Teams were formed from members of each postgraduate year (PGY) class. Competition tasks were level specific: knot tying for PGY-1, basic laparoscopy for PGY-2, handsewn bowel anastomosis for PGY-3, vascular anastomosis for PGY-4, and advanced laparoscopy for PGY-5. Task scores over a 4-year period (2014–2017) were analyzed and a survey of participating teaching faculty was conducted.Results Ten faculty members responded to the survey, for a response rate of 63%. A total of 50% respondents felt that the caliber of surgical skills increased since the Olympiad was implemented. Ninety percent agreed that the Olympiad was beneficial for residents to assess their skills against their peers. Over 4 years, there was an improvement in scores for suturing task, advanced laparoscopy, and bowel anastomosis (p < 0.05 for all three).Conclusion A residency-wide surgical skills competition can improve resident performance in technical tasks and promote faculty engagement in resident skills training.
Keywords: surgical simulation; surgical Olympiad; skills training; residency skills; residency training; surgical education